External Debt and Economic Growth: Two-Step System GMM Evidence for Sub-Saharan Africa Countries - Asafo, Shuffield Seyram; Matuka, Adelajda; Dominic, Nyendu (International Journal of Business, Economics and Management, 2019)
This paper examines external debt and economic growth relationship in a panel of 48 Sub-Saharan Africa countries (SSA) for the period 1990-2017 using a two-step system General Method of Moments (GMM) technique. Our study shows that contemporaneously, external debt has a negative and statistically significant impact on GDP growth. However, the first lag of external debt variables stimulates GDP growth. The implication is that external debt accumulated in the previous period makes funds available for growth enhancing expenditure in the next period. Furthermore, our study found no evidence of a non-linear relationship between debt and economic growth. Lastly, we found that the deleterious impact of external debt on GDP growth does not preclude poor or rich SSA countries. We recommend the adoption of state-of-the-art measures in collecting domestic revenue to complement external revenue sources. In addition, we advocate for strong macroeconomic environment in SSA so that yield negotiation on the debt will not dissipate the coffers of SSA countries via high debt servicing cost.